Self-Care Performance of Middle-Aged Stroke Patients in Korea. (March 2019) - Jang, Dong Eun; Shin, Juh Hyun
The incidence rate of middle-aged ischemic stroke patients has been increasing. Because of their high risk of recurrence, it is important for them to adhere to their self-care performance. The purpose of this study was to investigate predictors of self-care performance among middle-aged ischemic stroke patients. A descriptive correlational and cross-sectional survey design was used. About 140 participants who had been diagnosed with ischemic stroke within a year and visited neurological outpatients were investigated. Participants answered self-report questionnaires, the Secondary Stroke Prevention Knowledge Scale, the Health-Related Hardiness Scale, and the Subjective Self-Care Performance Scale. Hardiness, secondary-stroke-prevention knowledge, age, and stroke-diagnosis duration had statistically significant influences on self-care performance; hardiness had the largest effect. This study highlighted hardiness as the major predictor of self-care performance. To improve middle-aged ischemic stroke patients' self-care performance, nurses need an integrated approach that considers a patient's age, diagnosis duration, secondary-stroke-prevention knowledge, and, especially, hardiness.